Two-dimensional field theory and critical phenomena - Babich, A.V.; Klepikov, V.F. (Reports of the National Academy of Sciences of Ukraine, 2018)
A theory that allows one to describe the two-dimensional gravity is considered. Conditions, under which the theory has a hidden group of symmetry, are found. This group of symmetry allow one to simplify the corresponding equations and, under some conditions, to find the exact solutions.